INVESTIGATING STUDENTS’ KNOWLEDGE OF BASIC SCIENCE POSSESSED AS A PREDICTOR OF SENIOR SECONDARY SCHOOLS STUDENTS’ PERFORMANCE IN CHEMISTRY IN NASARAWA STATE - Kyala Istifanus; Dr. Samaila Hamza; Prof. M. M. Aliyu (Galaxy International Interdisciplinary Research Journal, 2022)
The study investigated the Students’ knowledge of Basic Science possessed as a predictor of their Senior Secondary School performance in Chemistry in Nasarawa State, Nigeria. The population of the study comprises of 3280 public Junior Secondary Schools Students who sat for BECE in 2016 and 1624 Public Senior Secondary Schools Students who also sat for Chemistry at SSCE (WAEC). A Correlation research design was used in this study. 265 students out of nine (9) Government Science Secondary Schools were sampled using the purposive sampling technique which formed the sample of the study. Secondary data was used in this study which was collected personally by the researcher from the selected Schools. BECE Basic Science and SSCE Chemistry (WAEC) results were used as instruments for data collection in this study. The data collected were analyzed using linear regression. The results from the data analysis revealed that Students’ knowledge of Basic Science at BECE is significant predictor of their performance in Chemistry at SSCE (WAEC). The study also found that Male students’ knowledge of Basic Science at BECE is not significant predictor of Male students’ performance in Chemistry at SSCE (WAEC). However, it was also found that Female students’ knowledge of Basic Science at BECE is significant predictor of Female students’ performance in Chemistry at SSCE. It was recommended among others that the teaching and learning of Basic Science at the Junior Secondary School should continue to have regular and proper supervision so as to ensure that students are able to perform better in SSCE Chemistry.